PERLAKUAN AKUNTANSI ASET BIOLOGIS TANAMAN APEL PADA PERKEBUNAN PT. KUSUMASATRIA AGROBIO TANI PERKASA (KUSUMA AGROWISATA) SESUAI IAS 41 AGRICULTURE - Sugianingtyas, Eka Hesty (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research tries to evaluate the accounting treatment of biological asset applied in PT. Kusumasatria Agrobio Tani Perkasa (Kusuma Agrowisata) based on IAS 41 Agriculture. This evaluation covers recognition, measurement, and reporting on biological asset carried out by a company based on the international accounting standard that regulates biological asset, that is IAS 41 Agriculture. The data is analyzed through qualitative descriptive method. The method analyzes the data through reviewing, presenting, studying, and explaining financial data in describing the accounting treatment on biological asset based on IAS 41. The results of this study show compatibility on the recognition of biological asset between the one applied by the company and the one by IAS 41. Further, inconformity in biological asset measurement is identified between the two. Kusuma Agrowisata uses historical cost in measuring the biological asset of apple orchard in hand because the company encountered difficulty in determining the fair value of its biological asset.Keywords: Biological Assets, Accounting Treatment, IAS 41.